1997
DOI: 10.1002/(sici)1099-1573(199706)11:4<299::aid-ptr99>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the essential oil ofCroton zehntneri, and its constituent estragole on intestinal smooth muscle

Abstract: The effects on isolated guinea‐pig ileum of the essential oil of Croton zehntneri (CZEO) and of its main constituent estragole (57% of CZEO by weight) were studied. CZEO and estragole (0.1–100 μg/mL) decreased the tonus in 56% and 61.5%, respectively, of the muscles. At concentrations above 10 μg/mL, they induced spontaneous rhythmic movements of small amplitude (less than 11% of the potassium contraction peak to peak). At concentrations from 1 to 100 μg/mL and with similar potencies, these agents blocked the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…24 The volatile oil of C. zehntneri has relaxing effect on smooth muscle, which supports the use of C. zehntneri in traditional medicine as a gastrointestinal antispasmodic, an activity that may in part be attributed to estragole. 28,29 …”
Section: Myorelaxant Antispasmodic and Anti-hypertensivementioning
confidence: 99%
See 1 more Smart Citation
“…24 The volatile oil of C. zehntneri has relaxing effect on smooth muscle, which supports the use of C. zehntneri in traditional medicine as a gastrointestinal antispasmodic, an activity that may in part be attributed to estragole. 28,29 …”
Section: Myorelaxant Antispasmodic and Anti-hypertensivementioning
confidence: 99%
“…is an aromatic plant native in northeastern Brazil, where it is popularly called "canelade-cunhã" and used in traditional medicine mainly as sedative, appetite stimulating, antianorexigen and for the relief of gastrointestinal disturbances; its bark and leaves are used as sweeteners in foods and drinks. 28,29 …”
mentioning
confidence: 99%
“…The major component of the extracts C. zehntneri was (E)-anethole reaching the content of 86.8% for the volatile oil. The content of methyl chavicol (estragole) that has been reported (Albuquerque et al, 1995;Coelho de Sousa et al, 1997) as the major component of C. zehntneri is well below the content of (E)-anethole and alpha-muurolene.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the volatile oil were different from that of pure anethole and estragole (methyl chavicol): the volatile oil enhanced the twitches evoked by nerve stimulation, estragole partially enhanced while anethole did not significantly induce the twitches. Coelho de Sousa, Barata, Magalhães, Lima, and Leal Cardoso (1997) studied the effects of the volatile oil and the estragole on guinea-pig ileum; the results have shown that the volatile oil has a predominantly antispasmodic effect on the intestinal smooth muscle, which is partially due to the presence of estragole. Coelho de Sousa, Criddle, and Leal Cardoso (1998) studied the effects of the volatile oil on the mechanical activity of various in vitro preparations of guinea-pig smooth muscle; the results gave support to the traditional use of C. zehntneri as a gastrointestinal antispasmodic.…”
Section: Introductionmentioning
confidence: 99%
“…Published research on plant extracts has focused primarily on the central nervous system (2,3) and on muscle (4)(5)(6)(7). We have previously shown that the essential oil of C. zehntneri (EOCz) exerts antispasmodic effects on guinea pig-isolated ileum (4,6), possibly explaining the use of C. zehntneri in the treatment of gastrointestinal problems.…”
mentioning
confidence: 99%